VIDAS D-dimer in combination with clinical pre-test probability to rule out pulmonary embolism - Carrier, Marc; Righini, Marc; Djurabi, Reza Karami; Huisman, Menno V.; Perrier, Arnaud; Wells, Philip S.; Rodger, Marc; Wuillemin, Walter A.; Gal, Grégoire Le (Thrombosis and Haemostasis, 2009)
Clinical outcome studies have shown that it is safe to withhold anticoagulant therapy in patients with suspected pulmonary embolism (PE) who have a negative D-dimer result and a low pre-test probability (PTP) either using a PTP model or clinical gestalt. It was the objective of the present study to assess the safety of the combination of a negative VIDAS© D-dimer result in combination with a non-high PTP using the Wells or Geneva models to exclude PE. A systematic literature search strategy was conducted using MEDLINE, EMBASE, the Cochrane Register of Controlled Trials and all EBM Reviews. Seven studies (6 prospective management studies and 1 randomised controlled trial) reporting failure rates at three months were included in the analysis. Non-high PTP was defined as “unlikely” using the Wells’ model, or “low/intermediate” PTP using either the Geneva score, the Revised Geneva Score, or clinical gestalt. Two reviewers independently extracted data onto standardised forms. A total of 5,622 patients with low/intermediate or unlikely PTP were assessed using the VIDAS D-dimer. PE was ruled out by a negative D-dimer test in 2,248 (40%, 95% confidence intervals [CI] 38.7 to 41.3%) of them. The three-month thromboembolic risk in patients left untreated on the basis of a low/intermediate or unlikely PTP and a negative D-dimer test was 3/2,166 (0.14%, 95% CI 0.05 to 0.41%). In conclusion, the combination of a negative VIDAS D-dimer result and a non-high PTP effectively and safely excludes PE in an important proportion of outpatients with suspected PE.
Keywords: D-dimer; diagnosis; management study; predictive value of tests; venous thromboembolism